Researching Design Learning - Kimbell, Richard. author. aut Link
XIV, 326 p.
Keywords: Design & Technology evolved in the school curriculum from the mid 1960s. By the 1980s it had become mainstream for the British government to fund research exploring what learners could do when challenged with design & technology tasks. The authors worked together on that project, producing in 1991 the first seminal research report on learners’ capability in design & technology. This book summarises the lessons learned from this and other projects. The book’s messages centre on the designing activity, on learning, teaching and assessment, and, more widely, on what can be learnt about the research process itself. The authors aim to answer questions such as: How does the active, concrete learning tradition enable cognitive and emotional growth? What influences bear upon the process; the teacher, the environment, the task, the learners themselves? Researching such questions, their concerns have integrated the conceptual, the practical and the pedagogic.